Determination of Tellurium by Electrothermal Atomic Absorption Spectrometry with Preconcentration by Co-Precipitation with Lanthanum Hydroxide - Cerutti, Estela Soledad (2005)
A procedure for the determination of traces of total tellurium is described which combines electrothermal atomic absorption spectrometry (ETAAS) with preconcentration of the analyte by coprecipitation. The samples, each spiked with lanthanum nitrate (20 mg L–1), are introduced into the Amberlite XAD-4 resin, and mixed with ammonium buffer (pH 9.1). Tellurium is preconcentrated by coprecipitation with the generated lanthanum hydroxide precipitate. The precipitate is quantitatively collected in the resin, and subsequently eluted with 5% (v/v) nitric acid. The determination is developed with ETAAS. Considering a sample consumption of 25 mL, an enrichment factor of 10 was obtained. The detection limit (3σ) was 0.04 μg L–1 and the precision (relative standard deviation) was 3.5% (n=10) at the 10-μg L–1 level. The calibration curve, using the preconcentration system for tellurium, was linear with a correlation coefficient of 0.9993. Satisfactory results were obtained for the determination of tellurium in the standard reference material NIST 1643d Trace Elements in Water and in a tap water sample.